Analisis Faktor–faktor yang Mempengaruhi Volume Ekspor Kopi Indonesia di Pasar Eropa - Kusumawati, Bening; Winarno, Sri Tjondro; Yuliati, Nuriah (Politeknik Negeri Lampung, 2026)
This study aims to analyze the key factors influencing the volume of Indonesian coffee exports to the European market from 2004 to 2023. As one of the world’s largest coffee exporters, Indonesia has experienced significant fluctuations in its export volume. Using multiple linear regression, the research examines the impact of three independent variables—rupiah-to-US dollar exchange rate, national coffee production, and the price of Indonesian coffee in the European market—on export volume, the dependent variable. Secondary data were sourced from official institutions, including Statistics Indonesia, FAO, ITC, and Bank Indonesia. The results indicate that all three variables have a positive and significant effect on export volume. The regression model explains 75.5% of the variation in export volume, with the remaining 24.5% influenced by external factors not included in the model. These findings underscore the importance of maintaining stable production, competitive pricing, and favorable exchange rates to enhance Indonesia’s coffee export competitiveness. The study provides strategic recommendations for stakeholders to enhance Indonesia’s coffee export performance by promoting production efficiency and macroeconomic stability through policies.